Environment-friendly chassis armor coating with strong adhesive force and preparation method thereof
By using specific composition and treatment methods of acrylic resin, epoxy resin and other auxiliary materials in aqueous chassis armor coatings, the problems of poor adhesion to carbon fiber chassis and prone to foaming at high temperatures are solved, and coatings with high adhesion, durability and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411801429.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
AI Technical Summary
The existing water-based chassis armor coatings have poor adhesion to carbon fiber chassis substrates, the coating film density is too high, and it is prone to bubble and cracking at high temperatures.
An environmentally friendly chassis armor coating with strong adhesion is used, and the composition includes 10 to 30 parts of acrylic resin, 10 to 30 parts of epoxy resin, 10 to 25 parts of filler, 5 to 10 parts of alcohol esters, 1 to 5 parts of dispersant, 0.1 to 1 part of silane coupling agent, 0.5 to 1 part of thickener and 30 to 60 parts of environmentally friendly solvent. The adhesion and durability of the coating are improved through specific component ratios and treatment methods.
It improves the adhesion, mechanical strength and durability of the coating, enhances the corrosion resistance of salt spray and wear resistance, improves the aggregation strength and foam resistance of the coating film, and is suitable for the carbon fiber chassis of new energy vehicles.
Smart Images

Figure CN119552548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating compositions, and in particular to an environmentally friendly chassis armor coating with strong adhesion and a preparation method thereof. Background Art
[0002] When a car is driving on a bad road, the bumps on the road may cause scratches and bumps on the bottom of the car, and further moisture, acid rain, and salt will corrode the metal chassis of the vehicle. Most of the electronics of new energy vehicles are distributed at the bottom of the car. In order to prevent the chassis from rusting and corrosion, which in turn causes damage to the battery and poses a safety hazard, some new energy vehicle chassis use a lighter high-strength carbon fiber chassis to replace the metal chassis, and add chassis armor coatings to prevent road conditions from damaging the vehicle chassis and protect the driving safety of the owner. With the technological advancement of water-based industrial coatings, the application of water-based industrial coatings has achieved rapid development, and people have begun to use more environmentally friendly and healthy water-based chassis armor coatings to replace oil-based chassis armor coatings.
[0003] However, after spraying, the existing water-based chassis armor coating has poor adhesion to the carbon fiber chassis substrate, and the coating film density is too high, which is prone to blistering and cracking at high temperatures. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an environmentally friendly chassis armor coating with strong adhesion and a preparation method thereof, aiming to solve the problems that the existing water-based chassis armor coating has poor adhesion to the carbon fiber chassis substrate after spraying, and the coating film density is too high, and it is easy to blister and crack at high temperature.
[0005] In order to achieve the above-mentioned purpose, the present invention provides an environmentally friendly chassis armor coating with strong adhesion. The environmentally friendly chassis armor coating with strong adhesion comprises, by weight: 10 to 30 parts of acrylic resin, 10 to 30 parts of epoxy resin, 10 to 25 parts of filler, 5 to 10 parts of alcohol ester dodecahydrate, 1 to 5 parts of dispersant, 0.1 to 1 part of silane coupling agent, 0.5 to 1 part of thickener, and 30 to 60 parts of environmentally friendly solvent.
[0006] In some embodiments, the monomers of the acrylic resin include methyl methacrylate, butyl acrylate, and methacrylic acid.
[0007] In some embodiments, the volume ratio of the methyl methacrylate, the butyl acrylate, and the methacrylic acid is (0.05-2):(3-5):(4-6).
[0008] In some embodiments, the coating includes 10-30 parts of a flame retardant, and the flame retardant is at least one of a phosphorus-based flame retardant, a diphenyl sulfone sulfonate, and an MCA flame retardant.
[0009] In some embodiments, the filler includes at least one of expanded graphite, magnesium hydroxide, titanium dioxide, calcium carbonate, and mica powder; and / or the average particle size of the filler is 8-25 μm.
[0010] In some embodiments, the environmentally friendly solvent includes ethylene glycol butyl ether and / or ethylene glycol diacetate, and water.
[0011] In order to achieve the above object, the present invention also proposes a method for preparing the above-mentioned environmentally friendly chassis armor coating with strong adhesion, comprising the following steps:
[0012] S1. Mixing an acrylic resin, an epoxy resin and an environmentally friendly solvent to form a first mixed solution of a preset volume concentration;
[0013] S2. The dispersant and flame retardant are added to the first mixed solution and stirred at a speed of 1500-2000 rpm to obtain a second mixed solution;
[0014] S3. Add the filler pretreated with silane coupling agent to the second mixed liquid and stir, then add thickener and alcohol ester twelve in sequence and stir at a speed of 500-1000 rpm to obtain an environmentally friendly chassis armor coating with strong adhesion.
[0015] In some embodiments, the preset volume concentration is 50% to 60%.
[0016] In some embodiments, in step S1, the preparation of the acrylic resin includes: distilling butyl acrylate, methacrylic acid, and methyl methacrylate under reduced pressure to remove impurities, and mixing to obtain a mixed monomer; adding a mixed solvent of n-butanol and ethylene glycol monobutyl ether to a reaction vessel, heating the temperature to 115°C to 125°C, adding the mixed monomer mixed with an initiator, and after the addition is completed within 2 hours, heating the temperature to 125°C to 135°C and continuing to keep warm for 1 hour, and vacuum drying to obtain an acrylic resin.
[0017] In some embodiments, in step S3, the pretreatment includes: diluting the silane coupling agent with a solvent, adjusting the pH value to 4-5.5, placing the ball-milled filler into a solid mixer, and spraying the silane coupling agent solution on the filler for stirring for 10-30 minutes, and drying to obtain the filler pretreated with the silane coupling agent.
[0018] Beneficial effects of the present invention: In the environmentally friendly chassis armor coating with strong adhesion provided by the present invention, acrylic resin provides good adhesion and weather resistance, while epoxy resin has excellent bonding performance and chemical stability. When they work together, the adhesion, mechanical strength and durability of the coating are improved; silane coupling agent, filler, and synergistic resin improve wet bonding force, enhance salt spray corrosion resistance, improve the cohesion strength of the coating film, improve anti-foaming property, enhance wear resistance and anti-permeability, and enhance the protective effect on the chassis; alcohol ester twelve as alcohol ester twelve can improve the film-forming performance of latex paint, reduce the minimum film-forming temperature, and improve scrub resistance. Under the mutual cooperation of the components, the environmentally friendly chassis armor provided by the present invention has high solid content, fast drying speed, excellent sealing, good adhesion, and is suitable for the carbon fiber chassis of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a preparation flow chart of an embodiment of the highly adhesive environmentally friendly chassis armor coating of the present invention.
[0020] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0021] In order to make the technical solutions and advantages of the present invention clearer, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods. The drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recorded in the claims.
[0022] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0023] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0025] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0026] Some new energy vehicle chassis use lighter high-strength carbon fiber chassis to replace metal chassis, and chassis armor coatings can prevent road conditions from damaging the vehicle chassis and protect the driving safety of car owners. With the technological advancement of water-based industrial coatings, the application of water-based industrial coatings has achieved rapid development, and people have begun to use more environmentally friendly and healthy water-based chassis armor coatings to replace oil-based chassis armor coatings. However, after spraying, the existing water-based chassis armor coatings have poor adhesion to the carbon fiber chassis substrate, and the film density of the coating is too high, which is prone to blistering and cracking at high temperatures.
[0027] In view of this, the present invention proposes an environmentally friendly chassis armor coating with strong adhesion. The environmentally friendly chassis armor coating with strong adhesion includes, by weight: 10 to 30 parts of acrylic resin, 10 to 30 parts of epoxy resin, 10 to 25 parts of filler, 5 to 10 parts of alcohol ester dodecahydrate, 1 to 5 parts of dispersant, 0.1 to 1 part of silane coupling agent, 0.5 to 1 part of thickener, and 30 to 60 parts of environmentally friendly solvent.
[0028] The molecular structure of acrylic resin contains a large number of carbon-carbon double bonds, which can participate in the cross-linking reaction during the curing process to form a three-dimensional network structure, thereby enhancing the mechanical strength and durability of the coating. In addition, acrylic resin has good transparency and gloss, and can provide a clear and bright coating effect. When used in conjunction with epoxy resin, acrylic resin can improve the flexibility of the coating and reduce stress cracks caused by temperature changes, thereby improving the impact resistance of the chassis armor coating.
[0029] The addition of epoxy resin significantly improves the adhesion between the coating and the chassis metal. The epoxy groups contained in the molecular structure of epoxy resin can form a hard cross-linked network. When used in combination with acrylic resin, it can balance the hardness and flexibility of the coating and improve the overall performance of the chassis armor coating.
[0030] The addition of fillers can improve the thickness and uniformity of the coating. The filler particles can fill the tiny gaps in the coating, reduce the porosity of the coating, improve the coating's anti-penetration, wear resistance and scratch resistance, and reduce the aging and degradation of the coating during long-term use.
[0031] Alcohol ester 12 can improve the flow and film formation of the coating, and can also promote the compatibility of other components in the coating and improve the overall performance of the coating. During the drying and curing process of the coating, alcohol ester 12 can act as part of the solvent to help the resin and filler in the coating to be evenly distributed, forming a uniform and dense coating structure.
[0032] Silane coupling agent, through its special structure, can form chemical bonds between organic materials and inorganic materials, which not only improves the adhesion between filler and resin, resin and carbon fiber substrate, but also improves the water resistance and chemical corrosion resistance of the coating, and enhances the durability of the coating.
[0033] Dispersants prevent pigments from agglomerating and settling, thereby improving the uniformity and stability of the coating. The addition of thickeners can reduce the flow and dripping of the paint during construction.
[0034] Through the mutual cooperation of the above components, the acrylic resin of the environmentally friendly chassis armor coating provides good adhesion and weather resistance, while the epoxy resin has excellent bonding performance and chemical stability. When they work together, the adhesion, mechanical strength and durability of the coating are improved; the silane coupling agent, filler, and synergistic resin improve the wet bonding force, enhance the salt spray corrosion resistance, improve the cohesion strength of the coating, improve the anti-foaming property, enhance the wear resistance and anti-permeability, and enhance the protective effect on the chassis; alcohol ester twelve as alcohol ester twelve can improve the film-forming performance of latex paint, reduce the minimum film-forming temperature, and improve the scrub resistance. Under the mutual cooperation of the components, the environmentally friendly chassis armor provided by the present invention has high solid content, fast drying speed, excellent sealing, good adhesion, and is suitable for the carbon fiber chassis of new energy vehicles.
[0035] In some embodiments, the dispersant includes at least one of Efka FA4663, YRFC-02, FS-01, DA-50.
[0036] In some embodiments, the silane coupling agent includes at least one of KH-550 silane coupling agent, KH-551 silane coupling agent, KH-560 silane coupling agent, and KH-570 silane coupling agent.
[0037] In some embodiments, the thickening agent includes at least one of hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
[0038] In some embodiments, the monomers of the acrylic resin include methyl methacrylate, butyl acrylate, and methacrylic acid.
[0039] As a hard monomer, methyl methacrylate can form a strong polymer chain during the polymerization process, improving the mechanical properties and weather resistance of the coating. Butyl acrylate has good fluidity and film-forming properties. As a soft monomer, it reduces cracks caused by temperature changes or mechanical stress. Methacrylic acid, as a functional monomer, introduces carboxyl functional groups to enhance the adhesion and cross-linking ability of the resin.
[0040] In some embodiments, the volume ratio of the methyl methacrylate, the butyl acrylate, and the methacrylic acid is (0.05-2):(3-5):(4-6).
[0041] In this scheme, on the one hand, the above three monomers are designed within the above volume ratio range taking into account the balance between the hardness and flexibility of the acrylic resin, the introduction of functional monomers and the copolymerization activity; on the other hand, the ratio of the three monomers can make the acrylic resin and the epoxy resin better compatible, forming a harmonious mixed resin system, which is conducive to the mixing of the remaining components.
[0042] In some embodiments, the volume ratio of methyl methacrylate, butyl acrylate, and methacrylic acid is any value in (0.05-2):(3-5):(4-6) such as 1:3:4, 1:3:5, 1:3:6, 1:4:6, 0.5:3:5, 1:4:5, 2:3:4, 2:5:5, etc. Preferably, the volume ratio of methyl methacrylate, butyl acrylate, and methacrylic acid is (0.05-1):(4-5):5. Preferably, the volume ratio of methyl methacrylate, butyl acrylate, and methacrylic acid is (0.05-1):(4-4.5):5.
[0043] In some embodiments, the coating includes 10-30 parts of a flame retardant, and the flame retardant is at least one of a phosphorus-based flame retardant, a diphenyl sulfone sulfonate, and an MCA flame retardant.
[0044] Phosphorus-based flame retardants include ammonium polyphosphate (APP), ammonium phosphate salts, phosphates and polyphosphates, phosphate esters, phosphaphenanthrene (DOPO), phosphazene compounds, organic phosphinic acids, organic phosphinic acid salts, and the like.
[0045] In some embodiments, the filler includes at least one of expanded graphite, magnesium hydroxide, titanium dioxide, calcium carbonate, and mica powder; and / or the average particle size of the filler is 8-25 μm.
[0046] Preferably, the filler includes expanded graphite or titanium dioxide. Expanded graphite as a filler improves the rheological properties of the coating and increases the flame retardant effect; the addition of titanium dioxide can improve the mechanical strength and adhesion of the thin spray layer, and improve the flame retardancy, electrical insulation and high temperature resistance of the coating. Within the average particle size range of 8-25 μm, the filler can be evenly dispersed in the coating.
[0047] In some embodiments, the environmentally friendly solvent includes ethylene glycol butyl ether and / or ethylene glycol diacetate, and water. In some embodiments, water accounts for 10-15 parts by weight. Using ethylene glycol butyl ether, ethylene glycol diacetate and water as solvents can effectively reduce volatile organic compound (VOC) emissions in coatings, reduce environmental pollution, improve construction safety, improve film performance, and reduce costs.
[0048] In order to solve the above problems, the present invention also proposes a method for preparing the above-mentioned environmentally friendly chassis armor coating with strong adhesion, comprising the following steps:
[0049] S1. Mixing an acrylic resin, an epoxy resin and an environmentally friendly solvent to form a first mixed solution of a preset volume concentration;
[0050] S2. The dispersant and flame retardant are added to the first mixed solution, and a high-speed disperser is introduced to disperse the mixed solution to ensure that the dispersant and flame retardant are evenly distributed in the coating, improve the uniformity and stability of the coating, and the speed is 1500-2000 rpm to obtain a second mixed solution;
[0051] S3. Add the filler pretreated with silane coupling agent to the second mixed liquid and stir, then add thickener and alcohol ester twelve in sequence and stir at a speed of 500-1000 rpm to obtain an environmentally friendly chassis armor coating with strong adhesion.
[0052] It should be noted that, in parts by weight, the environmentally friendly chassis armor coating with strong adhesion includes: 10 to 30 parts of acrylic resin, 10 to 30 parts of epoxy resin, 10 to 25 parts of filler, 5 to 10 parts of alcohol ester dodecahydrate, 1 to 5 parts of dispersant, 0.1 to 1 part of silane coupling agent, 0.5 to 1 part of thickener, 30 to 60 parts of environmentally friendly solvents, and 10 to 30 parts of flame retardants.
[0053] The stirring is completed by an electric stirrer, a high-speed disperser and the like. Mixing according to the above steps can form a stable coating and avoid aggregation or sedimentation of additives or fillers.
[0054] In some embodiments, the pre-treatment of carbon fiber composite materials for coating mainly adopts a treatment method of mechanical grinding after cleaning. The defects such as particles, pinholes, potholes and streaks generated by the molding process are removed by grinding, and a highly roughened surface is obtained, thereby increasing the contact surface of the coating to produce a "bite effect" and enhance the bonding force between the carbon fiber and the coating. After the coating forms a dry film, the dry film thickness is controlled at 300 to 800 μm.
[0055] In some embodiments, in step S1, the preset volume concentration is 50% to 60%.
[0056] In some embodiments, the preset volume concentration is 50%, 55%, 60%, or any value between 50% and 60%.
[0057] In some embodiments, in step S1, the preparation of the acrylic resin S101 includes: removing impurities from butyl acrylate, methacrylic acid, and methyl methacrylate by vacuum distillation, respectively, and mixing to obtain a mixed monomer; adding a mixed solvent of n-butanol and ethylene glycol monobutyl ether to a reaction vessel, heating to 115°C to 125°C, adding the mixed monomer mixed with an initiator, and after the addition is completed within 2 hours, heating to 125°C to 135°C and maintaining the temperature for 1 hour, vacuum drying, and obtaining an acrylic resin. In some embodiments, the volume of the initiator is less than or equal to 10% of the volume of the mixed monomer.
[0058] In some embodiments, in step S3, the pretreatment S301 includes: diluting the silane coupling agent with a solvent, adjusting the pH value to 4-5.5, placing the ball-milled filler into a solid mixer, and spraying the silane coupling agent solution on the filler for stirring for 10-30 minutes, and drying to obtain the filler pretreated with the silane coupling agent.
[0059] Example 1
[0060] Methyl methacrylate, butyl acrylate and methacrylic acid in a volume ratio of 1:4:5 are respectively subjected to reduced pressure distillation to remove impurities, and mixed to obtain a mixed monomer;
[0061] Add a mixed solvent of n-butanol and ethylene glycol monobutyl ether to a reaction vessel, raise the temperature to 120° C., add 10% of tert-butyl peroxide and the mixed monomer in a volume less than or equal to the volume of the mixed monomer, and after the addition is completed within 2 hours, raise the temperature to 130° C. and continue to keep the temperature for 1 hour, and vacuum dry to obtain an acrylic resin;
[0062] In parts by weight, 28 parts of acrylic resin, 28 parts of epoxy resin and 38 parts of environmentally friendly solvent (10 parts of water, 15 parts of ethylene glycol butyl ether, and 13 parts of ethylene glycol diacetate) are mixed to prepare a first mixed solution with a preset volume concentration;
[0063] Add 2 parts of DA-50 dispersant and 12 parts of sodium ammonium phosphate to the first mixed solution and stir, introduce a high-speed disperser to disperse the mixed solution at a speed of 1500-2000 rpm to ensure that the dispersant and the flame retardant are evenly distributed in the coating to obtain a second mixed solution;
[0064] 0.5 parts of silane coupling agent are diluted with solvent, and the pH value is adjusted to 4-5.5. 10 parts of ball-milled expanded graphite (average particle size is 10 μm) are placed in a HENSHEL high-speed solid mixer, and KH-550 silane coupling agent solution is sprayed on the expanded graphite and stirred at a speed of 1500-2000 rpm for 10-30 minutes, and dried to obtain a filler pretreated with a silane coupling agent;
[0065] Add the filler pretreated with silane coupling agent to the second mixed liquid and stir, heat to 155°C, then add 0.5 parts of hydroxymethyl cellulose and 6 parts of alcohol ester twelve in sequence and stir, adjust the speed to 500-1000 rpm, react for 1.5 hours, and obtain an environmentally friendly chassis armor coating with strong adhesion.
[0066] Butyl acrylate (BA), methacrylic acid (MAA), methyl methacrylate (MMA): reagent grade; Epoxy resin 604 (EP-604): epoxy value 0.09-0.14, industrial grade, Jiangsu Sanmu Group.
[0067] Example 2-3
[0068] In Example 2-3, except that the components used to prepare the environmentally friendly chassis armor coating with strong adhesion are added as shown in Table 1, the rest refer to Example 1.
[0069] Comparative Example 1
[0070] Only 56 parts of acrylic resin were used, and the rest was as in Example 1.
[0071] Comparative Example 2
[0072] Only 56 parts of epoxy resin were used, and the rest were as in Example 1.
[0073] Comparative Example 3
[0074] The solvent was replaced with γ-valerolactone and water, and the rest was the same as in Example 1.
[0075] Comparative Example 4
[0076] The volume ratio of methyl methacrylate, butyl acrylate and methacrylic acid is 3:5:7, and the rest is as in Example 1.
[0077] Table 1. Components of Examples and Comparative Examples (parts by weight)
[0078]
[0079]
[0080] Performance Testing
[0081] 1. The first mixed solution prepared in Example 1-3 was tested for resin compatibility using the co-solvent method.
[0082] Take part of the first mixed solution and apply it on a glass plate with an applicator to a film thickness of 200 μm. Place it at 23°C for 2 weeks to form a film. Visually inspect the transparency of the film. Leave the remaining solution to stand for 2 days and observe whether it is stratified.
[0083] 2. The chassis armor coatings prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to solid content tests and drying speed tests, and then coated on carbon fiber samples (purchased from China Hengrui), with the dry film thickness controlled to 800 μm, and related performance tests were performed:
[0084] 1. Solid content: Tested in accordance with GB / T 1725-2007;
[0085] 2. Surface drying time: Tested in accordance with GB / T 1728-1979;
[0086] 3. Impact strength performance: Tested in accordance with GB / T 1732-1993;
[0087] 4. Adhesion: Tested according to GB / T 9286-1998;
[0088] 5. Abrasion resistance: tested according to ASTM D4060 standard, CS-17 rubber grinding wheel, load 1Kg, cycle 3000 times;
[0089] 6. Sagging performance test: The chassis armor coatings in each embodiment and comparative example were sprayed on a carbon fiber plate with a spray gun, and the spraying thickness was controlled to be 4 mm. Then the sprayed side was placed vertically, and the flow of the coating was observed by visual inspection;
[0090] 7. High temperature resistance test: Tested according to ASTM D648 standard, tested at 250℃, 0.45MPa for 400h.
[0091] Table 2. Performance test results
[0092]
[0093]
[0094] It can be seen from the data in Table 2 that the solid contents of Comparative Examples 1, 2 and 4 are relatively low, which may be due to an improper ratio of resin to solvent or the low quality of the resin itself. Low solid content will affect the drying speed, adhesion and wear resistance of the coating.
[0095] In Comparative Example 3, due to the use of different solvents (γ-valerolactone and water), resin compatibility problems occurred, thus affecting the transparency and delamination of the coating.
[0096] The longer surface drying time of Comparative Example 2 may be caused by uneven distribution of fillers, which may affect the early performance of the coating and ultimately lead to poor wear resistance and adhesion.
[0097] Comparative Examples 1 and 2 use only a single type of resin, while the example uses a mixture of acrylic resin and epoxy resin, and the mixed use provides better overall performance.
[0098] The above test results confirm that in the environmentally friendly chassis armor coating with strong adhesion provided by this scheme, acrylic resin provides good adhesion and weather resistance, while epoxy resin has excellent bonding performance and chemical stability. When they work together, the adhesion, mechanical strength and durability of the coating are improved; silane coupling agent, filler, and synergistic resin improve wet bonding force, enhance salt spray corrosion resistance, improve the cohesion strength of the coating, improve anti-foaming, enhance wear resistance and anti-permeability, and enhance the protective effect on the chassis; alcohol ester twelve as alcohol ester twelve can improve the film-forming performance of latex paint, reduce the minimum film-forming temperature, and improve scrub resistance. Under the mutual cooperation of the components, the environmentally friendly chassis armor provided by the present invention has high solid content, fast drying speed, excellent sealing, good adhesion, and is suitable for the carbon fiber chassis of new energy vehicles.
[0099] Those skilled in the art may combine and associate different embodiments or examples and features of different embodiments or examples described in this specification without mutual contradiction.
[0100] The above description is only a partial or preferred embodiment of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.
Claims
1. An environmentally friendly chassis armor coating with strong adhesion, characterized in that: In parts by weight, the highly adhesive environmentally friendly chassis armor coating comprises: 10-30 parts of acrylic resin, 10-30 parts of epoxy resin, 10-25 parts of filler, 5-10 parts of alcohol ester dodecahydrate, 1 to 5 parts of dispersant, 0.1 to 1 part of silane coupling agent, 0.5-1 part thickener, 30-60 parts of environmentally friendly solvent.
2. The environmentally friendly chassis armor coating with strong adhesion as claimed in claim 1, characterized in that: The monomers of the acrylic resin include methyl methacrylate, butyl acrylate and methacrylic acid.
3. The environmentally friendly chassis armor coating with strong adhesion as claimed in claim 2, characterized in that: The volume ratio of the methyl methacrylate, the butyl acrylate and the methacrylic acid is (0.05-2):(3-5):(4-6).
4. The environmentally friendly chassis armor coating with strong adhesion as claimed in claim 1, characterized in that: The coating comprises 10-30 parts of a flame retardant, and the flame retardant is at least one of a phosphorus-based flame retardant, a diphenyl sulfone sulfonate, and an MCA flame retardant.
5. The environmentally friendly chassis armor coating with strong adhesion as claimed in claim 1, characterized in that: The filler comprises at least one of expanded graphite, magnesium hydroxide, titanium dioxide, calcium carbonate and mica powder; And / or, the average particle size of the filler is 8-25 μm.
6. The environmentally friendly chassis armor coating with strong adhesion as claimed in claim 1, characterized in that: The environmentally friendly solvent includes ethylene glycol butyl ether and / or ethylene glycol diacetate, and water.
7. A method for preparing an environmentally friendly chassis armor coating with strong adhesion, characterized in that: The steps include: S1. Mixing an acrylic resin, an epoxy resin and an environmentally friendly solvent to form a first mixed solution of a preset volume concentration; S2. The dispersant and flame retardant are added to the first mixed solution and stirred at a speed of 1500-2000 rpm to obtain a second mixed solution; S3. Add the filler pretreated with silane coupling agent to the second mixed liquid and stir, then add thickener and alcohol ester twelve in sequence and stir at a speed of 500-1000 rpm to obtain an environmentally friendly chassis armor coating with strong adhesion.
8. The method for preparing the environmentally friendly chassis armor coating with strong adhesion as claimed in claim 7, characterized in that: In step S1, the preset volume concentration is 50% to 60%.
9. The method for preparing the environmentally friendly chassis armor coating with strong adhesion as claimed in claim 7, characterized in that: In step S1, the preparation of the acrylic resin includes: Butyl acrylate, methacrylic acid and methyl methacrylate are respectively subjected to reduced pressure distillation to remove impurities, and then mixed to obtain a mixed monomer; Add a mixed solvent of n-butanol and ethylene glycol monobutyl ether to a reaction vessel, raise the temperature to 115° C.-125° C., add the mixed monomer mixed with an initiator, and after the addition is completed within 2 hours, raise the temperature to 125° C.-135° C. and continue to keep the temperature for 1 hour, and vacuum dry to obtain an acrylic resin.
10. The method for preparing the environmentally friendly chassis armor coating with strong adhesion as claimed in claim 7, characterized in that: In step S3, the pretreatment includes: diluting the silane coupling agent with a solvent, adjusting the pH value to 4-5.5, placing the ball-milled filler in a solid mixer, and spraying the silane coupling agent solution on the filler for stirring for 10-30 minutes, and drying to obtain the filler pretreated with the silane coupling agent.
Citation Information
Patent Citations
Water-based epoxy modified acrylic resin for plastic paint and preparation method thereof
CN109180877A
Water-based acrylic resin for coil coating, and preparation method and application thereof
CN112011242A
Acrylic water-based coating material for color steel plate and preparation method thereof
CN113845788A
Cited By
Nano indium-iron microcrystalline adhesive and curing process
CN120442199A
Carbon fiber connecting glue and curing process
CN122648042A